2023
DOI: 10.3390/su15076328
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation, Regional Disparities and Driving Mechanisms of High-Quality Agricultural Development in China

Abstract: Based on China’s new development philosophy and the connotation of high-quality agricultural development, this study constructed a six-dimensional comprehensive evaluation framework: innovation-effectiveness-sustainability-coordination-openness-sharing. The spatio-temporal-range-improved entropy approach and the Dagum Gini coefficient were applied to evaluate and analyze the level of regional disparities and the dynamic distribution characteristics of high-quality agricultural development in China in the perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Zhang et al (2023) [21] constructed an agricultural water resources evaluation system to evaluate agricultural water resources carrying capacity and analysis of its spatio-temporal variation in Henan Province, China. Wang et al (2023) [22] constructed a six-dimensional comprehensive evaluation framework: innovation-effectiveness-sustainability-coordination-openness-sharing to evaluate and analyze the level of regional disparities and the dynamic distribution characteristics of high-quality agricultural development in China in the period from 2010 to 2018. It can be found that most of the current research on the spatio-temporal evolution of agricultural sustainability focuses on a certain aspect of agriculture or explores the impact of certain factors on agricultural development.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2023) [21] constructed an agricultural water resources evaluation system to evaluate agricultural water resources carrying capacity and analysis of its spatio-temporal variation in Henan Province, China. Wang et al (2023) [22] constructed a six-dimensional comprehensive evaluation framework: innovation-effectiveness-sustainability-coordination-openness-sharing to evaluate and analyze the level of regional disparities and the dynamic distribution characteristics of high-quality agricultural development in China in the period from 2010 to 2018. It can be found that most of the current research on the spatio-temporal evolution of agricultural sustainability focuses on a certain aspect of agriculture or explores the impact of certain factors on agricultural development.…”
Section: Introductionmentioning
confidence: 99%